Achieving safety and weight reduction in automobiles with the application of composite material. (2022) - Sateesh, N.; Subbiah, R.; Nookaraju, B.Ch; Siva Nagaraju, D.
Abstract: In the present scenario of cutthroat competition in automobile industry, the importance for sleek and efficient models of automobiles with aesthetics and passenger comfort is paramount. In addition to the comforts like air conditioning and spaciousness etc., the 'suspension' is also significant in the selection of an automobile. The main focus of this paper is on weight reduction by replacing conventional spring steels with composite materials. A successful attempt has been made at Gokaraju Rangaraju Institute of Engineering and Technology, Hyderabad laboratories to fabricate the composite leaf spring, which is having equivalent properties of Maruti800 car leaf spring. The transverse failures in steel leaf springs lead to rear axle dislocation. This problem could be successfully eliminated with composite leaf springs since the general failure in unidirectional reinforcement composites is in longitudinal direction. This paper suggests the design improvements in this direction.